Work in Progress: How Real is Student Engagement in using Virtual Laboratories - Lindsay, Euan; Koretsky, M.; Richardson, J.; Mahalinga-Iyer, M. (Stipes Publishing LLC, 2007)
Laboratory classes are an integral part of engineering education, but they are resource intensive and can also impose significant logistical constraints upon the curriculum. One option to reduce these burdens is the use of virtual laboratories where students do not interact with real hardware, but rather with computer simulations of laboratory equipment. A key issue in virtual laboratories is the issue of the authenticity of the learning experience. It is imperative that the students interact with these laboratories in a way that is reflective of the hardware being simulated. However, there is the potential for students to lose sight of the underlying hardware, and instead get caught up in the "computer game-ness" of the experience. The degree to which students are engaged in the type of cognitive processes used by practicing engineers is critical to how they construct their learning within the virtual laboratory, and as such can dramatically impact the overall learning outcomes of the class. This WIP paper presents a multi-site study investigation into these outcomes involving four different virtual laboratories at four different universities.